2011
DOI: 10.3389/fendo.2011.00096
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies in Childhood Craniopharyngioma

Abstract: Craniopharyngiomas are biologically benign lesions (WHO Grade 1) of the sellar and suprasellar region, associated with a serious morbidity. About 50% of these tumors become clinically apparent during childhood. Clinical symptoms include headaches, chiasm syndrome, hydrocephalus, pituitary insufficiencies, and obesity. Growth arrest is a typical symptom in children. The treatment of craniopharyngiomas includes surgery as well as radiotherapy. The goal of surgery varies according to the tumor location and extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 50 publications
(57 reference statements)
1
32
0
2
Order By: Relevance
“…With the aid of imaging studies, recent reports have indicated that the degree of obesity is positively correlated with the degree and extent of hypothalamic damage [39,[56][57][58]. Taking these considerations into account, a novel classification of pre-surgical involvement and post-surgical lesions of hypothalamic structures based on MRI was recently published [39,59]. The classification might help to establish more risk-adapted surgical strategies (FIGURE 2).…”
Section: Hypothalamic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aid of imaging studies, recent reports have indicated that the degree of obesity is positively correlated with the degree and extent of hypothalamic damage [39,[56][57][58]. Taking these considerations into account, a novel classification of pre-surgical involvement and post-surgical lesions of hypothalamic structures based on MRI was recently published [39,59]. The classification might help to establish more risk-adapted surgical strategies (FIGURE 2).…”
Section: Hypothalamic Dysfunctionmentioning
confidence: 99%
“…Depending on the tumor extension, section 2 can be reached by transcranial as well as transsphenoidal procedures. Modified with permission from [59], Frontiers Endocrinology. the prevalence of obesity is higher, reaching up to 55% [14,17,21,49,51,[61][62][63].…”
Section: Obesity and Eating Disordersmentioning
confidence: 99%
“…Craniopharyngiomas are classified as histologically benign tumors (WHO Grade 1 tumors) [1]. Nevertheless, the infiltrative behavior of the lesion may hamper its definitive treatment and often implies unfavorable and long-term sequelae after surgical removal [2].…”
Section: Introductionmentioning
confidence: 99%
“…For favorably localized childhood craniopharyngioma (i.e., without involvement of hypothalamic or optical structures), the treatment of choice is an attempt at complete resection with preservation of visual and hypothalamic function (Choux and Lena, 1979;Fahlbusch et al, 1999;Flitsch et al, 2011). For unfavorably localized tumors, which are too close to or too entangled with the optic nerve and/or the hypothalamus, controversy exists over whether complete resection should still be attempted, or whether a planned, limited resection (biopsy, partial/subtotal resection) should be performed (Muller, 2010a(Muller, , 2011aBuchfelder et al, 2013).…”
Section: Treatment Strategies Neurosurgery E Strategies and Effectsmentioning
confidence: 99%